Room filled with Beckman System TR Enzyme Activity Analyzers (1973)
The instruments filling this room -- Beckman Instruments' System TR, introduced in 1973 -- were the first automated analyzer for clinical enzymes. The two men in the background of this image are unidentified.
Keywords: Medical laboratories--Equipment and supplies; Scientific apparatus and instruments; Enzymes--Analysis; Beckman Instruments, Inc.; Medical instruments and apparatus